(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, we propose an explicit measure for the growth rate of an algorithm complexity function. This measure complements the usual time or space complexity analysis of algorithms and can fill a gap in the understanding of the asymptotic notation and thus, provide educational benefits. First, we discuss some properties of the growth measure, such as its behavior with respect to linear operators. Second, we analyze its connection to the asymptotic complexity notations and discuss its implications.